Study on the multifunctional evaluation of cultivated land and the evolution of trade-off/synergy relationships in the Sanjiang Plain - Wang, Yuwei; Zhao, Yinghui; Guo, Jingpeng; Qi, Yanping (Frontiers in Environmental Science, 2025)
As the core functional carrier of land resources, cultivated land has a dynamic feedback mechanism between its production, ecological and other functions, and land changes. Analyzing the trade-offs/synergies among cultivated land functions and formulating differentiated zoning control plans is of great significance for achieving sustainable utilization of the land system. Using grids as evaluation units, this paper quantitatively evaluates the production function, living security function, ecological function, and landscape function of the cultivated land in the Sanjiang Plain for 2005, 2010, 2015, and 2020. The Spearman correlation coefficient method and the bivariate spatial autocorrelation analysis method are adopted to reveal the trade-off/synergy among various functions of the cultivated land. Functional zoning is carried out through self-organizing mapping (SOM) to explore the dynamic evolution of each functional zone and propose corresponding development goals and optimization strategies. The findings indicate that: (1) Between 2005 and 2020, the production function continued to increase, and the living security, ecological, and landscape functions showed a trend of fluctuating increase. (2) There are significant trade-offs or synergy relationships among various functions. The functional synergy between the production-living security function and the production-landscape function is most significant. The trade-off between ecological and production functions is the most prominent. (3) This paper innovatively proposes to divide the Sanjiang Plain into six types of cultivated land functional areas, namely, the agriculturally balanced development area; the agro-ecological leisure area; the eco-agricultural development area; the agricultural potential improvement area; the agricultural production-dominated area; and the agricultural living security area, and constructively puts forward the development countermeasures for each functional area. The research results not only reflect the dynamic changes in the functions of cultivated land in the Sanjiang Plain, but also the functional zoning results can provide a scientific basis for the differentiated management and control of regional cultivated land.